Pathogen profile of urinary tract infections in Nephrology Unit - Chojeta, Dariusz; Smarz-Widelska, Iwona; Koziol, Malgorzata M. (Current Issues in Pharmacy and Medical Sciences, 2021)
Urinary tract infection (UTI) is one of the most common types of infection in both hospitalized and outpatient settings. The etiology is mostly bacterial, and the typical causative agent is uropathogenic Escherichia coli. There is a noticeable increase in drug resistance of pathogenic microorganisms. The aim of the study was retrospective analyses of etiological agents of UTI and their antibiotic resistance patterns in Nephrology Unit patients. Material and methods: An infection was diagnosed based on the patient's symptoms and positive results of urine culture, carried out over 26 months. The clinical material was tested by using the VITEK system, the drug susceptibility of the emerged pathogens was identified. Results: The most common etiological agents of UTI were Gram-negative rods: Escherichia coli (51.23%), Klebsiella spp. (19.3%) and Proteus spp. (13.68%). The analysis of drug resistance profiles of these pathogens showed a high percentage of strains resistant to broad-spectrum penicillins and fluoroquinolones. At the same time, it seems that E. coli isolates presented the most favorable pattern of drug susceptibility in this comparison. Conclusions: The alarming tendency of increasing drug resistance among pathogens causing UTIs to antibiotics such as penicillins or fluoroquinolones prompts a careful choice of drugs in empirical therapies. The most appropriate practice in this regard seems to be meticulous control of nosocomial infections and making therapeutic decisions based on the knowledge of local microbiological data.